To determine which expressions could evaluate to \( \frac{1}{64} \), we need to evaluate each expression one by one:
-
\((1/2)^{-5}\) \[ (1/2)^{-5} = (2)^{5} = 32 \] This does not equal \( \frac{1}{64} \).
-
\(6^{-4}\) \[ 6^{-4} = \frac{1}{6^4} = \frac{1}{1296} \] This does not equal \( \frac{1}{64} \).
-
\((1/4)^{-3}\) \[ (1/4)^{-3} = (4)^{3} = 64 \] This does not equal \( \frac{1}{64} \).
-
\(4^{-3}\) \[ 4^{-3} = \frac{1}{4^3} = \frac{1}{64} \] This equals \( \frac{1}{64} \).
-
\(2^{-6}\) \[ 2^{-6} = \frac{1}{2^6} = \frac{1}{64} \] This also equals \( \frac{1}{64} \).
The two expressions that evaluate to \( \frac{1}{64} \) are:
- \(4^{-3}\)
- \(2^{-6}\)
So the correct options are:
- \(4^{-3}\)
- \(2^{-6}\)